PENGEMBANGAN MEDIA PROMOSI DIGITAL DESAIN DALAM USAHA PT. PARCELINE PACK - Kezia, Imanuella; Irdha Yunianto (CV. KAMPUS AKADEMIK PUBLISING, 2025)
In today's era that has advanced with its sophisticated technology, many companies use all their promotional media in digital form which has a big influence on increasing the company's sales. Social media is one of the promotional fields that is widely used by all groups both abroad and domestically. Packaging design has also become one of the aspects that is widely sought after and pursued by many business people in increasing the selling value of products through attractive and creative packaging. Parceline Pack is one of the companies engaged in the field of packaging and hampers. Parceline Pack also often receives orders in the form of Level hampers, Tanjung flower boxes, Emina hampers and many more.